Vaccinal prevention of Tick-Borne Encephalitis in chelyabinsk Region: Dynamics of Vaccination, population Immunity, Analysis of TBE cases in Vaccinated persons - S. V. Luchinina; A. I. Semenov; O. N. Stepanova; V. V. Pogodina; S. G. Gerasimov; M. S. Shcherbinina; L. I. Kolesnikova; T. A. Suslova (Эпидемиология и вакцинопрофилактика)
The Chelyabinsk Region (Southern Urals) is high endemic territory. The TBE incidence is 3.57 ± 1.7 per 100 000 of population. A level of vaccination against TBE increased from 0.3 to 34.8% in 1999 - 2013. Specific immunity of population in 35.9% is connected with vaccination, in 64.1% with natural immunity consequently latent contact with TBE virus. Dynamics of vaccinal prevention, increasing of population immunity in different landscapes, and in different age groups were studied. 77.7% of TBE patients did not vaccinated, 18.2% received of specific immunoglobulin at postexposition and 3.7% persons were vaccinated. Unusual lethal case in patient, who received 8 doses of vaccine is analysed in this article.